Analysis of Textual Analysis Methods In Appkication Game - Fernando F; Susanty W (International Conference on Engineering and Technology Development (ICETD), 2017)
Play is an essential element for the development of children's physical, emotional, mental, intellectual, creative, and social. School-age children are the age groups or often referred to as the age of conformity. During the development of school-age children, the most desirable games are games that are competitive. School age children develop the ability to play games (games) with the regulations. Along with the rapid development of Internet technology, gaming is also experiencing rapiddevelopment. The game has a huge impact that game players formed themselves into more challenged in several electoral decisions in winning action games played . Addiction game characterized by the extent of excessive game players can affect negatively the player of the game. The number of emerging games that are created to fulfill the desire of gamers, making the author wants interested to know how researchers or designing games and analyzes, Based on the above statement to besuccessful in building a game requires a proper analysis to determine the function of the game. The main goal made the strategic planning of information systems is to analyze the purpose of gamers in playing the game. The main objective of the Games is to facilitate the utilization of analyzing and identifying game design fit for gamers to play games. Main data traits that can be used in the Games are gamers aged teens to adults who already have a high potential tendency to play games, meaning the data is composed of phenomena or trends that make gamers very interested in these games. The methods discussed in the construction of Games in this paper is a method Textual Analysis. Textual Analysis method, textual analysis is a way for researchers to gather information about how the human world. It is a methodology of data collection, for those researchers who want to understand where members of various culture and subculture understand who they are, and how they are into the world in which they live. Textual analysis is useful for researchers working in cultural studies, media studies, mass communication, and perhaps even in sociology and philosophy. When we perform a textual analysis of the text, we make educated guesses that the most likely interpretation of possible text, text Interpreting (television programs, magazines, advertisements, and so on). This study discusses the Games and textual analysis method used to build an application Games. Based on the description above, the writer gave the title "Analysis of Textual Analysis Methods in Application Games"